Bridging the gap between Acme and UML for CBD - Goulão, Miguel; Brito e Abreu, F. (Workshop on Specification and Verification of Component-Based Systems (SAVCBS'2003), co-located with ESEC/FSE'2003, 2003)
Architecture Description Languages (ADLs) such as Acme (a mainstream second generation ADL which contains the most common ADL constructs) provide formality in the description of software architectures, but are not easily reconciled with day-to-day development concerns, thus hampering their adoption by a larger community. UML, on the other hand, has become the de facto standard notation for design modeling, both in industry and in academia. In this paper we map Acme modeling abstractions into UML 2.0, using its new component modeling constructs, its lightweight extension mechanisms and OCL wellformedness rules. The feasibility of this mapping is demonstrated through several examples. This mapping bridges the gap between architectural specification with Acme and UML, namely allowing the transition from architecture to implementation, using UML design models as a middle tier abstraction.